WINDS OF CHANGE AND THE FUTURE OF EUROPEAN DEFENCE - Leandro, Francisco José (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
This paper poses questions about EU soft power, why it is insufficient and how that can be changed. This is done in an attempt to shed light on the current status of the European Union defence sector. The paper specifically addresses political, strategic, structural and organizational challenges. It further proposes development paths for the enhancement of common defence capacities, vis-a-vis the current stage of major threats and the parity of strategic contenders such as the USA, the People’s Republic of China and the Russian Federation. Finally, this paper identifies concrete policy recommendations for a sustainable long-term defence cooperation-integration process, compatible with the exercise of the EU’s 27 national sovereignties. The research methods are undergirded by qualitative research and supported by semi-structured interviews. Seminar discussions and key points were also incorporated into the final version.